PENGATURAN MINERAL DAN BATU BARA DI INDONESIA ; PERSPEKTIF LINGKUNGAN HIDUP DALAM KONSTITUSI (GREEN CONSTITUTION) - Fachri Fadillah (2023)
The supreme agreement of a nation is committed to the constitution, and therefore it is essential to be a benchmark for the state to behave, to determine the current direction and purpose of the environment is a world issue, in which the whole world is concerned with the current environmental issues, it is only fitting that environmental norms be brought to the highest accord of the nation, that all the policies taken by the state, the direction of development, Social interaction does not go unnoticed by the surroundings around it. The mineral and coal-mining industries, which are both income and private sector contributors to governments, According to an agreement on environmental values of the highest laws, the study USES a normative-based approach combined with a conceptual approach that also USES a secondary qualitative data the study concludes on how the mineral and coal Settings in Indonesia from a green constitution perspective and whether the mineral and coal arrangements in Indonesia are affected by environmental damage from this study is the mineral control And coal in Indonesia is now in 2020's number 3 act, which in several chapters relating to its license indicates could cause environmental damage, which is not in harmony with green constitution. Keywords: Green Constitution, Mineral and Coal, Environment